KOMPETENSI PROFESIONAL GURU TAMAN KANAK-KANAK DI KOTA PONTIANAK - Yuni, Dayang Uci Parida; Fadillah, Fadillah; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was conducted to determine the professional competence of kindergarten teachers in Pontianak. The research method used was descriptive with a quantitative research form. The data source of this study was a kindergarten teacher. The sample used in this study was 78 kindergarten teachers with a certified civil servant status. The data collection techniques was indirect communication techniques with data collection tools in this study are questionnaires and documentation. Then, collected data was analyzed using quantitative data analysis techniques with central tendency formula  Mean, Mode, and Standard Deviation. Based on the results of data analysis the professional competence of kindergarten teachers about learning mastery in Pontianak was in the category of "Medium" which is indicated by a percentage of 64% with an average amount of 6.58 and the total average of 3 indicators of learning mastery was 3.79 (It means from 78 teachers there are 50 teachers who master the characteristics). Curriculum Mastery was included in the category of "medium" which is indicated by a percentage of 51% with an average number of 2.51 and the total average of three indicators of curriculum mastery was 1.34 (It means from 78 teachers there are 40 teachers who master the curriculum). Mastery of ethical insight and professional development in the category of “Medium" as indicated by a percentage of 54% with an average number of 2.53 and the total average of  three indicators of mastery of ethical insight and professional development was 1.66 (It means from 78 teachers there are 42 teachers who are good at communicating with students).  Keywords: Professional Competence, Kindergarten Teacher